THE INFLUENCE OF MUSIC RECOMMENDATION ALGORITHMS ON ADOLESCENT SELF-IDENTITY IN THE DIGITAL STREAMING ERA - Nirwansyah Revan F; Ahmad Zion Alfattah; Faiq Abrisam S; Ahmad Fadhil Muzaki L; Nurjamiaty (Bulletin of Engineering Science, Technology and Industry, 2025)
Abstract*